Development of an integrated electronic module with Al-Qur’an verses using the Canva Application on static fluids - Nurfitriani; Astra Patriot, Evelina; Isnaini, Muhammad (Research in Physics Education, 2023)
This study aims to determine the validity and practicality of the Integrated Physics Electronic Module of Al-Qur’an Verses Using Canva Applications on Static Fluids. This research was conducted at one public senior high school in Indonesia. The data collection technique in this study used Random Sampling. Research subjects used two groups, one control group and one experimental group. The validation results from the experts resulted that majority of several experts such as teaching material experts, learning media experts, language experts, integration experts, and educators have argued that this module was appropriate to be used in teaching of static fluids. This meant his module was valid to be used in the physics learning in the context of static fluid. In addition, students’ responses to the use of this module showed that they have argued that this module was very practical to enhance students’ understanding in statics fluids.